2007
DOI: 10.1523/jneurosci.4035-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

ERG Conductance Expression Modulates the Excitability of Ventral Horn GABAergic Interneurons That Control Rhythmic Oscillations in the Developing Mouse Spinal Cord

Abstract: During antenatal development, the operation and maturation of mammalian spinal networks strongly depend on the activity of ventral horn GABAergic interneurons that mediate excitation first and inhibition later. Although the functional consequence of GABA actions may depend on maturational processes in target neurons, it is also likely that evolving changes in GABAergic transmission require fine-tuning in GABA release, probably via certain intrinsic mechanisms regulating GABAergic neuron excitability at differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(95 citation statements)
references
References 65 publications
4
91
0
Order By: Relevance
“…Indeed, while there was no correlation between the absolute power in each frequency between EEG and EMG, we found a significant correlation between the ratio of the power in lower and higher frequencies in the SMC-EEG and the same ratio in the relative power of the ROP-EMG. However, the capacity for spinal motoneuronal pools to oscillate at higher frequencies is also dependent upon fast synaptic inhibition and developmental changes in the pattern of spinal inhibition will also influence their intrinsic oscillatory activity and may account, at least in part, for the frequency shift (O'Sullivan et al, 1991;Mc Donough et al, 2001;Furlan et al, 2007;Sibilla and Ballerini, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, while there was no correlation between the absolute power in each frequency between EEG and EMG, we found a significant correlation between the ratio of the power in lower and higher frequencies in the SMC-EEG and the same ratio in the relative power of the ROP-EMG. However, the capacity for spinal motoneuronal pools to oscillate at higher frequencies is also dependent upon fast synaptic inhibition and developmental changes in the pattern of spinal inhibition will also influence their intrinsic oscillatory activity and may account, at least in part, for the frequency shift (O'Sullivan et al, 1991;Mc Donough et al, 2001;Furlan et al, 2007;Sibilla and Ballerini, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Intracortical inhibition is not mature until adulthood and is reduced in the elderly (Peinemann et al, 2001;Mall et al, 2004;Walther et al, 2009). The morphological properties of alpha-motoneurons and their excitatory and inhibitory control mature during development and are altered in the elderly (O'Sullivan et al, 1991;Erim et al, 1999;Mc Donough et al, 2001;Mentis et al, 2002;Furlan et al, 2007;Carlin et al, 2008;Sibilla and Ballerini, 2009). Finally, both the diameter and excitability of corticospinal axons increase during adolescence Müller and Hömberg, 1992) while white matter hyperintensities within the corticospinal tract become prevalent in old age (Moscufo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…) were identified and studied with a standard high [K ϩ ] o extracellular solution (S 3 ; calculated Nernst equilibrium potential for K ϩ , Ϫ32.5 mV) (Sacco et al, 2003;Furlan et al, 2007;Hirdes et al, 2005),…”
Section: Methodsmentioning
confidence: 99%
“…However, gating properties vary substantially between endogenous and heterologously expressed ERG channels and between subunits (Pond and Nerbonne, 2001;Hirdes et al, 2005). So far, neuronal ERG currents have been described in cerebellar Purkinje neurons (Sacco et al, 2003) and ventral horn interneurons (Furlan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports showed the ability of risperidone or ceramide to suppress I K(IR) in pituitary GH 3 cells (14,15). Pharmacological blockade of this current in the CNS has been recently noted to result in changes in neuronal excitability that would alter synaptic integration (16,17). Alternatively, several studies reported that ranolazine can block the human ether-à-go-go-related gene (HERG) K + current expressed in Xenopus oocytes and in HEK293 cells (18,19).…”
Section: +mentioning
confidence: 99%